Peningkatan Kapasitas Aparatur Desa melalui Pelatihan Penataan Administrasi di Desa Rinbesihat Kecamatan Tasifeto Barat Kabupaten Belu - Yoakim Rembu; Alfrido Naiheli; Nikolaus Uskono; Herminus Kefi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
The village is the lowest level of government that directly interacts with the community in providing and delivering public services. This requires the support of competent village officials, who are able to provide transparent and accountable services. Orderly and professional village administration is a crucial foundation for achieving good village governance. However, village administration issues remain a significant challenge that requires serious attention. This Community Service activity aims to improve the capacity of village officials in public service through administrative training in Rinbesihat Village, West Tasifeto District, Belu Regency. This community service activity involved university students and was implemented in several stages: initial coordination with the sub-district and village governments, problem mapping, activity implementation, and evaluation. The results of this community service activity were increased knowledge, which in turn improved the quality of village officials in village administration. With this training, it is hoped that village administration management can become more orderly, effective, and support the achievement of good and accountable village governance.